A circle with center (xo, yo) and radius r has an equation of the form:
(x - xo)2 + (y - yo)2 = r2
which can be rearranged to:
x2 - 2xox + xo2 + y2 - 2yoy + yo2 = r2
⇒ x2 - 2xox +y2 - 2yoy + xo2 + yo2 - r2 = 0
or x2 - 2xox +y2 - 2yoy = r2 - xo2 - yo2
So depending how your equation is given, the center can be read directly from the equation (first form above) or is -1/2 times the coefficients of the x and y terms. eg:
What is the center of the circle with equation x2 - 4x + y2 + 6y + 12 = 0
The coefficients of the x and y terms are -4 and +6, so the center is -1/2 times these, namely; (2, -3).
Fully rearranging the circle's equation:
x2 - 4x + y2 + 6y + 12 = 0
⇒ (x - 2)2 - 4 + (y + 3)2 - 9 + 12 = 0 [completing the squares]
⇒ (x - 2)2 + (y + 3)2 - 1 = 0
⇒ (x - 2)2 + (y + 3)2 = 1
⇒ circle has centre (2, -3) and radius 1.
Equation of the circle: (x-3)^2 +( y+13)^2 = 169
There are probably several ways to approach it; one general equation for the circle is: (x - a)2 + (y - b)2 = r2 This describes a circle with center at coordinates (a, b), and with a radius of r.
to be honest I dont know
x2+y2+4x+2y+3=0(x+2)2 + (Y+2.5)2 = 3This is the equation of circle with center at (-2,-2.5) with radius 3.5
The equation of a circle with center (0,2) and radius r is x^2+(y-2)^2=r^2 Since it passes through (0,0) (the origin) 0^2+(0-2)^2=r^2 r^2=4 The equation of the circle is x^2+(y-2)^2=4
a diameter
The center of the circle is at (9, 7) on the Cartesian plane
Equation of the circle: (x-3)^2 +( y+13)^2 = 169
(3, -2) You find the center by taking the opposite of the numbers added to the X and to the Y.
multiple the diameter by 2 to get the radius, then use your equation and go from there
There are probably several ways to approach it; one general equation for the circle is: (x - a)2 + (y - b)2 = r2 This describes a circle with center at coordinates (a, b), and with a radius of r.
to be honest I dont know
x2+y2+4x+2y+3=0(x+2)2 + (Y+2.5)2 = 3This is the equation of circle with center at (-2,-2.5) with radius 3.5
The equation of a circle with center (0,2) and radius r is x^2+(y-2)^2=r^2 Since it passes through (0,0) (the origin) 0^2+(0-2)^2=r^2 r^2=4 The equation of the circle is x^2+(y-2)^2=4
2 pi rthis is the equation of the circumference of a circle. just multiply out 2 times pi(3.14159) times the radius that you were given.
Square feet are a measure of area, and the area of a circle is usually given by the equation: a = πr2 The circumference of a circle is given with the equation: c = 2πr To find the area of the circle given only it's circumference, we can rearrange the circumference equation, solving it for r, and then substituting it into our radius equation in place of r. c = 2πr r = c / 2π a = πr2 a = π(c / 2π)2 a = πc2 / 4π2 a = c2/π So the area of a circle is equal to the square of it's circumference divided by pi.
The area of a circle is given by the equation A=πr2.To solve for r, divide both sides by π, then take the square root of both sides of the equation.This leaves you with the equation r=sqrt(A/π)